Cutting Temperature Study And Temperature Distribution in the Cutting Wedge - Urinov Nasillo Fayzilloevich; Saidova Mukhabbat Khamroevna; Ramazonov Azizbek Chori ugli (Genius Journals, 2022)
The article presents an analysis of the durability of the cutting tool depending on the temperature of the working surfaces of the tool.
Keywords: workpiece; cutting wedge; front surface; cutter